Dielectric Properties and AC Conductivity Measurements of Amorphous Ge15Se85 Glass - Balbir Singh Patial; Neha; Jai Prakash; Rajesh Kumar; S.K. Tripathi; Nagesh Thakur (Журнал нано- та електронної фізики)
In the present study, investigations of dielectric parameters viz dielectric constant (), dielectric loss () and AC conductivity measurements have been made for bulk chalcogenide Ge15Se85 glass in the frequency range 10 to 500 kHz within the temperature range from 300 to 390 K. The variation of dielectric constant and dielectric loss with frequency at room temperature is reported and discussed in the investigated glassy binary alloy.